2020
DOI: 10.1038/s41598-019-57317-7
|View full text |Cite|
|
Sign up to set email alerts
|

Combined spatiotemporal and frequency-dependent shear wave elastography enables detection of vulnerable carotid plaques as validated by MRI

Abstract: Fatal cerebrovascular events are often caused by rupture of atherosclerotic plaques. However, ruptureprone plaques are often distinguished by their internal composition rather than degree of luminal narrowing, and conventional imaging techniques might thus fail to detect such culprit lesions. In this feasibility study, we investigate the potential of ultrasound shear wave elastography (SWE) to detect vulnerable carotid plaques, evaluating group velocity and frequency-dependent phase velocities as novel biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…All studies scored an unknown or high risk of bias in at least one category. Seven studies (Ramnarine et al 2014b;Garrard et al 2015;Li et al 2016;Zhang et al 2016;Alis et al 2018;Shang et al 2018;Marlevi et al 2020) did not report whether they included patients randomly or consecutively, and one study reported they did not (Marais et al 2019). In addition, most studies (Li et al 2016;Zhang et al 2016;Lou et al 2017;Marais et al 2019) did not report whether the index test was interpreted without knowledge of the reference standard and vice versa.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies scored an unknown or high risk of bias in at least one category. Seven studies (Ramnarine et al 2014b;Garrard et al 2015;Li et al 2016;Zhang et al 2016;Alis et al 2018;Shang et al 2018;Marlevi et al 2020) did not report whether they included patients randomly or consecutively, and one study reported they did not (Marais et al 2019). In addition, most studies (Li et al 2016;Zhang et al 2016;Lou et al 2017;Marais et al 2019) did not report whether the index test was interpreted without knowledge of the reference standard and vice versa.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…In human studies, push frequencies and imaging rates were not reported, except for an imaging frame rate of 8 kHz by Marais et al (2019). Marlevi et al (2020) applied a dual-sided push pulse of 400 ms simultaneously triggered in the leftand right-hand sides of the region of interest (ROI). Marais et al (2019) applied three supersonic pushes of 100 ms at three depths 5 mm apart along the centerline of the ROI, including the anterior and posterior wall.…”
Section: Applied Ultrasound Techniquesmentioning
confidence: 99%
See 3 more Smart Citations